2008
DOI: 10.1002/pen.21080
|View full text |Cite
|
Sign up to set email alerts
|

Super‐ductile PBT alloy with excellent heat resistance

Abstract: A super-ductile PBT alloy with excellent heat resistance was successfully fabricated by reactive blending of poly(butylene terephthalate) (PBT) with poly(ethylene-coglycidyl methacrylate) together with linear low density polyethylene (LLDPE) and hydrogenated styrene-butadiene-styrene block copolymer (SEBS). It possesses a unique tensile stress-strain curve with no yielding point and large elongation at break, moreover, the alloy did not show serious deterioration of the mechanical properties by high temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…A similar T g depression at low temperature ranges is also reported in other polymeric systems composed of rubber‐toughened glassy polymers, for example, acrylonitrile‐butadiene‐styrene copolymer,46 styrene‐rich styrene‐butadiene diblock copolymers,47 and poly(butylene terephthalate) blended with poly(ethylene‐ co ‐glycidyl methacrylate) and linear low‐density polyethylene 48. Inoue and coworkers48 reported that the T g depression of the rubbery component results in significant enhancement of ductility.…”
Section: Resultssupporting
confidence: 80%
“…A similar T g depression at low temperature ranges is also reported in other polymeric systems composed of rubber‐toughened glassy polymers, for example, acrylonitrile‐butadiene‐styrene copolymer,46 styrene‐rich styrene‐butadiene diblock copolymers,47 and poly(butylene terephthalate) blended with poly(ethylene‐ co ‐glycidyl methacrylate) and linear low‐density polyethylene 48. Inoue and coworkers48 reported that the T g depression of the rubbery component results in significant enhancement of ductility.…”
Section: Resultssupporting
confidence: 80%
“…It has been previously shown that poly(styrene‐ b ‐(ethylene‐ co ‐butylene)‐ b ‐styrene (SEBS) can toughen semicrystalline polymers, such as poly(lactic acid) (PLA) and poly(butylene terephthalate) (PBT) [1, 2]. However, both neat PLA and neat PBT become very brittle by high‐temperature annealing.…”
Section: Introductionmentioning
confidence: 99%
“…For these semicrystalline polymers, the embrittlement is probably caused by crystallization; for example, a decrease of the amount of amorphous material and an increase in crystal lamellar thickness, and the physical aging of amorphous region. For PBT, the effect of crystallization was negligibly small [2], and the embrittlement is mostly due to physical aging.…”
Section: Introductionmentioning
confidence: 99%
“…For the rubber phase an evident T g depression was observed in the P100H and P70H30X blends, where rubber is present in discrete domains. Many research studies have reported the depression of the rubber T g in systems consisting of microspherical inclusions of a rubber in a rigid plastic matrix . In such systems, the difference in the thermal contraction between the two phases would generate a negative pressure in the rubber phase, which results in an increase of the free volume and correspondingly a decrease of the T g of the rubber phase.…”
Section: Resultsmentioning
confidence: 99%